Proposta de modelo de negócio integrador de práticas circulares para a indústria têxtil - Santos, Renato Alessandro Rocha (2022)
Business models have gained increasing prominence in scientific research, as they describe how a company creates, captures and delivers value, and once associated with the circular economy, they gain unique characteristics such as circular inputs, resource recovery, life extension, sharing, and product service system. In this context, there is no integration of the various practices of circular business models, making it difficult to effectively recycle products. This job aimed to develop a model that integrates all practices found in circular business models in the textile industry, based on a bibliometric and systematic review. To evaluate the model, the Delphi method was used, which consisted of selecting specialists from the textile industry, who, through a questionnaire, issued their opinions regarding the proposed model, reaching a consensus after two rounds. As a theoretical contribution, a systematic review was carried out, which resulted in six types of circular business models for the textile industry, making it possible to propose and validate by the Delphi method, a business model that integrates circular practices for the textile industry, with twenty-six practices. Eighteen practices were also identified as trends and eight more as market practices in the Brazilian textile industry. In addition to identifying the Virtualization practice as non-adherent in the Brazilian textile industry, and finally, six circular business models for the textile industry were identified. As a practical contribution, the proposed model can contribute to the management of a textile company, mainly in the recovery of resources. In this way, practices that did not receive consensus can contribute to strategic management, and to organizational practice, as well as practices that received consensus in the first round, act in the recovery of resources, providing a new product. On the other hand, operational managers need to prepare for the Virtualization practice, due to lack of investment. As a contribution to society, the use of the proposed model can contribute to the optimization of textile waste, promoting recycling that can replenish production, reducing the extraction of new resources. Nonetheless, scenario virtualization can promote better planning, but it is necessary to investigate the feasibility of implementation due to its cost, and the diversity of circular business models can contribute to environmental and economic aspects.